Analisa dan Perancangan Optimasi Jaringan dengan Metode Wireles Distribution System - Sidik Rohmanto; Saiful Bahri; Wisnu Sanjaya (Universitas Boyolali, 2022)
designing an internet network that utilizes wireless lines to expand the network area coverage that is able to cover the entire area of ​​the Walen Village Office building is the goal of the research. The internet network design that the researcher uses is a network design with a WDS wireless distribution system model. The results of the design of the internet network with the WDS (Wireless distribution system) model will be tested for 7 days with 3 tests every day, namely 07.00-08.00